Evaluation of IPM modules on soybean defoliators and leaf miner - Rathod, P K; Bhosle, B B (Indian Journal of Plant Protection, 2020)
The field experiments were conducted during Kharif season of the year 2009 and 2010 to study the influence of different IPM modules on incidence of Spodoptera litura, semilooper and Aproaerema modicella Deventer on soybean at Department of Entomology, Marathwada Krishi Vidyapeeth, Parbhani (Maharashtra, India). The experiment comprising MAU IPM modules, NRCS IPM module, BIPM module, chemical control and untreated control was laid out in randomized block design with four replications. The results based on pooled data revealed significantly minimum per cent defoliation in MAU module (12.7 %) followed by NRCS module(13.7 %) and chemical control treatment (13.9 %) which were found at par with each other and significantly superior over BIPM module and untreated control. However, the next best module was BIPM (16.2 %) which was found to be statistically significant over untreated control. Significantly minimum per cent leaflet damage due to leaf miner was observed in MAU module (8.2 %) followed by NRCS module (8.8 %) and chemical control treatment (9.2 %). The highest I.C.B.R. 1:4.91 was obtained in MAU IPM module, followed by NRCS IPM module (1:4.73) and chemical control (1:3.71).